2022
DOI: 10.3390/life12071002
|View full text |Cite
|
Sign up to set email alerts
|

An Electro–Microbial Process to Uncouple Food Production from Photosynthesis for Application in Space Exploration

Abstract: Here we propose the concept of an electro–microbial route to uncouple food production from photosynthesis, thereby enabling production of nutritious food in space without the need to grow plant-based crops. In the proposed process, carbon dioxide is fixed into ethanol using either chemical catalysis or microbial carbon fixation, and the ethanol created is used as a carbon source for yeast to synthesize food for human or animal consumption. The process depends upon technologies that can utilize electrical energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Conceptually, a biorefinery operating in the manner described could even provide the fertilizer needed to grow the biomass feedstock or the nitrogen source needed to grow yeast biomass within the process. The potential to grow yeast and other microbes as nutritious protein sources using basic carbon molecules plus urea and salts has recently been discussed by others [60] and demonstrated in our laboratory [45]. These advances open the way to consider biorefineries as an integrated source of microbial protein for food, plus chemicals including those for broader applications as fuels.…”
Section: A Model Lignocellulosic Bio/chemicals Refinery Delivering Fo...mentioning
confidence: 80%
See 1 more Smart Citation
“…Conceptually, a biorefinery operating in the manner described could even provide the fertilizer needed to grow the biomass feedstock or the nitrogen source needed to grow yeast biomass within the process. The potential to grow yeast and other microbes as nutritious protein sources using basic carbon molecules plus urea and salts has recently been discussed by others [60] and demonstrated in our laboratory [45]. These advances open the way to consider biorefineries as an integrated source of microbial protein for food, plus chemicals including those for broader applications as fuels.…”
Section: A Model Lignocellulosic Bio/chemicals Refinery Delivering Fo...mentioning
confidence: 80%
“…Although soybean is rich in dietary protein, it contains antinutritional factors, including phytates, tannins, trypsin inhibitors, and oligosaccharides that negatively impact, e.g., iron absorption [43,44]. High protein-containing yeasts can circumvent these antinutritional problems by providing the necessary amino acid balance, together with essential B vitamins and dietary fiber [45]. Moreover, S. cerevisiae produces phytase activities that can reduce iron binding issues associated with soybean meal [46].…”
Section: A Food and Fuel Lignocellulosic Biorefinery That Sequesters ...mentioning
confidence: 99%
“…Engineered yeast will be essential to nutritional diversity in space, ensuring that a range of tastes, flavours, aromas (Van Wyk et al, 2018) and colours negate the risk of dietary fatigue. Altered carbon source utilisation will be essential to wholly circularise waste management on any resource‐isolated extraterrestrial destination (Bell et al, 2022; Espinosa et al, 2020). As yeast research and technology matures, it may be feasible within a few decades to produce a ‘colony starter kit’ consisting of a consortia of engineered yeast with pan‐genomic diversity through carefully selected neo‐chromosomes layered over minimal genome architectures.…”
Section: Synthetic Yeast Futuresmentioning
confidence: 99%
“…Furthermore, studies have shown that microgravity conditions do not seem to significantly affect its growth or viability 17 , and work conducted by NASA has highlighted the potential for engineered S. cerevisiae as a useful source of essential nutrients for human health and nutrition (e.g., NASA’s BioNutrients project). Recent estimates of the nutritional value of a vitamin-prototrophic yeast strain in the context of human space travel suggest that all vitamins and macronutrients necessary for a balanced human diet could be provided for 50–100 people per day from a single 3000 L fermentation 18 . All this makes S. cerevisiae a promising candidate for developing into a microbial food-production system (Fig.…”
Section: Microorganisms As Space Foodmentioning
confidence: 99%
“…Alternatively, a more mature technological possibility involves the electrochemical reduction of carbon dioxide with hydrogen to form methanol in a process already commercialized on Earth by the company Carbon Recycling International. Given that the yeast Pichia pastoris can grow efficiently on methanol (growth rate of 0.15/h) 25 , and there are strains of S. cerevisiae that can grow efficiently on ethanol made from a similar process 18 , the electrochemical reduction of CO 2 with hydrogen poses a promising solution to the recycling of waste carbon to food in a space-travel setting. Once these problems are solved, this process could become very attractive since liquid carbon sources are easier to store and are more easily utilized in a bioreactor.…”
Section: Recycling Of Essential Microbial Nutrientsmentioning
confidence: 99%